Upaya Peningkatan Keandalan Penyulang dengan Manuver Jaringan - Slamet Nurhadi; Muhammad Fahmi Hakim; Ruwah Joto (Politeknik Negeri Malang, 2023)
The Tlogosari feeder was disturbed 20 times so that the reliability of system wasn’t said to be good. The purpose of this research was to make efforts to increase reliability and reduce ENS by maneuvering the network and adding CO Branch. Hoped that after these efforts the reliability level of Tlogosari Feeder will be better and ENS will be as minimal as possible. The network maneuver is carried out by delegating part of Tlogosari Feeder load when it experiences a disturbance to the nearest feeders on the condition that the total load current after the maneuver doesn’t exceed the current setting and conductor ampacity. The addition of CO Branch is based on fault data to localize fault points to reduce transformer outages. After performing network maneuvers and adding CO Branch in the sub-networks, it was found that the SAIDI and SAIFI values were improved and the ENS was reduced. Network maneuvering and addition of CO Branch are quite effective in implementing the Tlogosari Feeder.